Interfacial tuning of magnetic anisotropy for low-power spintronic memory devices - Astha Khandelwal; Suchit Kumar Jena; Lei Wan; Alan Kalitsov; Rajesh Vilas Chopdekar; Derek A. Stewart; Tiffany S. Santos; Bhagwati Prasad (APL Materials, 2025)
Interfacial engineering of magnetic anisotropy is crucial for the development of low-power spintronic memory devices. In thin-film magnetic heterostructures, perpendicular magnetic anisotropy (PMA) supports high-density data storage by reducing device dimensions while maintaining thermal stability and data retention, whereas voltage-controlled magnetic anisotropy (VCMA) facilitates energy-efficient data writing. However, achieving simultaneous optimization of PMA and VCMA is challenging due to their reliance on intricate interfacial parameters and synthesis conditions. This study presents a systematic strategy to modulate spin–orbit coupling (SOC) strength at the CoFeB/MgO interface by incorporating an iridium heavy-metal layer and precisely tuning the thickness of CoFeB and Ir. Through post-deposition annealing, we engineer the SOC to simultaneously enhance PMA and VCMA, addressing critical limitations in the design of voltage-driven magnetoresistive devices. These findings highlight the significance of interfacial tuning in improving the performance and energy efficiency of spintronic memory technologies, paving the way for their integration into next-generation data storage systems.